Closed venereology wards in the GDR. (10th June 2016) - Schochow, M.; Steger, F.
Abstract: Background: At least 10 closed venereology wards existed in the GDR. To this date, the history of these wards has not yet been investigated thoroughly. Objective: The history of the closed venereology wards in the GDR will be reconstructed by taking those in Halle (Saale) and Leipzig‐Thonberg as examples. At the centre of the examination are the daily routines, the medical treatment and the education of the women. Methods: Extensive archival research was conducted and the historical sources were critically evaluated. Moreover, interviews were held with women who had been admitted against their will as well as with former physicians, nurses and administrative staff members of the closed venereology wards. Results: In most cases, the women were taken at random and admitted to the closed venereology wards by the police. They were not informed about the purpose, type and possible side‐effects of their medical treatment. It was performed without their consent and therefore constituted a violation of their physical integrity. Even though 70% of the women had not been diagnosed with a sexually transmitted disease (STD), all of them had to undergo a gynaecological examination on a daily basis. The daily routine was strict, and the women were kept under surveillance. The wards had the 'educative' goal of transforming the women into 'socialist personalities'. Conclusion: The women in the closed venereology wards fell victim to politicized medicine. Put differently, medical care was supplemented with educational intentions and concepts, the purpose of which was to transform 'suffering persons' into 'socialist personalities'. This disciplinary system was based on terror. The closed venereology wards were not all alike; in some wards the women had to carry out chores on a daily basis (Halle/Saale), while in other wards they were detained and isolated from the outside world (Leipzig‐Thonberg).